Pengaruh Social Campaign Terhadap Brand Loyalty dengan Brand Image Sebagai Variabel Intervening Pada Kopi Kalyan - Lestari, Ardisa Dwi Putri; Astono, Anjar Dwi (Research and Community Service UNIVERSITAS KALBIS, 2023)
This study explains the influence of Social Campaign on Brand Loyalty with Brand Image as an intervening variable. This study used a quantitative approach by distributing questionnaires to 140 respondents which were then processed using the SPSS 26 program. Sampling used a non-probability sampling technique with purposive sampling. The results of the hypothesis test show that Social Campaign has a significant effect on Brand Image, while Brand Image has a significant effect on Brand Loyalty. However, the Social Campaign has no direct effect on Kopi Kalyan's Brand Loyalty, but requires mediation from Brand Image. Based on the results of hypothesis testing, the indirect effect of Social Campaign on Brand Loyalty through Brand Image is 40.7%. The implications of this research can provide input so that Kopi Kalyan can pay attention to the factors that influence Brand Loyalty and their brand image.